Employment of the Programs (3DS MAX & MARVELOUS DESIGNER) in Draping the Pleats on the Mannequin - Dr. Salia Hassan Abdullah Khafaji (مجلة العصر للعلوم الانسانية والاجتماع, 2022)
Draping on the mannequin is considered one of the arts that belong to the Plastic Arts, and it is also considered one of the most important methods that help the fashion designer in achieving his ideas, it is a realistic and practical method that helps in creating and designing fashion, In addition to the ability to judge the suitability of designs and innovative ideas for the implementation process, in addition to judging the suitability of the design for the different bodies patterns, in addition to the above, the experience of dealing with the materials that used with a delicate and high artistic sense with all the different technical possibilities that can be carried. The recommendations of this study is to Seeking for all that is new in studying the art of draping on the mannequin and discovering more computer programs, and to experimenting the draping on the virtual mannequin with various types of materials, and also to employing the universities and the higher institutes in the Kingdom of Saudi Arabia and urging them to procedure more research and studies that serve the industry.